2018
DOI: 10.1002/slct.201801685
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive Bimetallic Gold–Silver Nanoparticles Production in a Research Nuclear Reactor

Abstract: Synthesis of radioactive, bimetallic nanoparticles was successfully accomplished using the Missouri S&T research nuclear reactor (MSTR). Aqueous solutions of 2 mM gold chloride and 2 mM silver nitrate were prepared and mixed with a solution of 1 mM polyvinylpyrrolidone and 60 mM of 2‐propanol. Four different samples with volume ratios of 70/30, 50/50, 30/70, and 0/100 of Au/Ag were irradiated at a reactor thermal power of 10 kW for 3 min. The morphology, crystal structure, and chemical composition of the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The synthesis of 198 Au nanoparticles usually involves two steps: neutron activation of Au foil and preparation of [ 198 Au]­HAuCl 4 followed by chemical reduction and stabilization. Garcia Toro and coauthors proposed an alternative, one-step, radiation-induced synthetic procedure for the production of radioactive AuNPs and bimetallic nanoparticles by combining neutron and γ-irradiation, allowing the simultaneous reduction and activation of Au ions in aqueous solution. , γ-rays trigger the radiolytic reduction of water and the subsequent formation of different species such as OH – , H • , H 2 O 2 , and hydrated electrons, which have the potential to reduce Au 3+ and form AuNPs. The authors also demonstrated that it was possible to obtain bimetallic alloy and core–shell nanoparticles by adding silver nitrate to the Au solution prior to irradiation.…”
Section: Radiolabeled Nanomaterials As Therapeutic Agentsmentioning
confidence: 99%
“…The synthesis of 198 Au nanoparticles usually involves two steps: neutron activation of Au foil and preparation of [ 198 Au]­HAuCl 4 followed by chemical reduction and stabilization. Garcia Toro and coauthors proposed an alternative, one-step, radiation-induced synthetic procedure for the production of radioactive AuNPs and bimetallic nanoparticles by combining neutron and γ-irradiation, allowing the simultaneous reduction and activation of Au ions in aqueous solution. , γ-rays trigger the radiolytic reduction of water and the subsequent formation of different species such as OH – , H • , H 2 O 2 , and hydrated electrons, which have the potential to reduce Au 3+ and form AuNPs. The authors also demonstrated that it was possible to obtain bimetallic alloy and core–shell nanoparticles by adding silver nitrate to the Au solution prior to irradiation.…”
Section: Radiolabeled Nanomaterials As Therapeutic Agentsmentioning
confidence: 99%